Superiority of Fault-Caused-Speed-Fluctuation-Based Dynamics Modeling: An Example on Planetary Gearbox with Cracked Sun Gear - Xiaoqing Yang; Guolin He; Canyi Du; Lei Xu; Junjie Yu; Haiyang Zeng; Yanfeng Li (Machines)
A planetary gear fault generates periodic speed fluctuations, which significantly influence its vibration signal. It is a necessity to explore the vibration modulation features of gear faults to provide an effective indicator for fault detection. Therefore, a superior rigid-flexible coupling dynamics model of a planetary gearbox involving the fault-caused speed fluctuation is developed, where the meshing stiffness under the impact of fault-caused speed fluctuation is innovatively deduced utilizing the potential energy method; then, the meshing stiffness is substituted into the rigid dynamics model to calculate the excitation forces. Transfer path functions from excitation locations to the sensor installed on the housing are obtained by considering the modal parameters of the flexible housing. Finally, the excitation forces are combined with their transfer path functions to calculate the vibration signal. The fault modulation features of the cracked sun gear deduced by the superior dynamics model emerge surrounding the meshing frequency and its harmonics, as well as the resonance ranges, which can be a reliable sign for identifying faults. The experiment conducted on a single-stage planetary gearbox confirms the validity and superiority of the proposed model, which holds significant value for guiding fault detection and prognosis in planetary gearboxes.